2017
DOI: 10.1007/s11523-017-0538-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of B-Cell Maturation Antigen in the Biology and Management of, and as a Potential Therapeutic Target in, Multiple Myeloma

Abstract: B-cell maturation antigen (BCMA) was originally identified as a cell membrane receptor, expressed exclusively on late stage B-cells and plasma cells (PCs). Investigations of BCMA as a target for therapeutic intervention in multiple myeloma (MM) were initiated in 2007, using cSG1 as a naked antibody (Ab) as well as an Ab-drug conjugate (ADC) targeting BCMA, ultimately leading to ongoing clinical studies for previously treated MM patients. Since then, multiple companies have developed anti-BCMA-directed ADCs. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…BCMA and TACI may compete for ligand and/or provide signals that regulate the effects of BAFF-R. Thus, deficiency of these 2 receptors may exacerbate BAFF-R-driven survival mechanisms that lead to the B cell hyperplasia underlying CVID ILD (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…BCMA and TACI may compete for ligand and/or provide signals that regulate the effects of BAFF-R. Thus, deficiency of these 2 receptors may exacerbate BAFF-R-driven survival mechanisms that lead to the B cell hyperplasia underlying CVID ILD (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…BCMA is also expressed at much lower concentrations (9-to 50-fold lower) by plasmacytoid dendritic cells, which are known to help promote MM PC survival in the bone marrow environment [13,17]. Additional details regarding the role of BCMA in B-cell biology and in MM, including illustrations, can be found in other reviews [18][19][20][21].…”
Section: Biology Of Bcma In MMmentioning
confidence: 99%
“…For example, one study found that patients with a complete response (CR) had lower sBCMA levels (median, 38.9 ng/mL) than patients with a partial or minimal response (median, 99.7 ng/mL) or nonresponsive disease (median, 195.3 ng/mL) [29]. Because sBCMA has a much shorter serum half-life (24-36 h) compared with Mprotein (3-4 weeks), changes in sBCMA more rapidly reflect changes in disease status than M-protein levels and therefore may serve as a useful alternative and potentially more sensitive marker for monitoring disease status [20,34]. Notably, sBCMA levels do not appear to change more significantly in response to one particular class of anti-MM therapy over others [7].…”
Section: Bcma As a Tool For Prognosis And Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…However, the variable density of BCMA on MM cells in different patients and the propensity of target escape after initial BCMA-targeting immunotherapy may compromise therapeutic efficacy. For example, BCMA on the cell surface can be cleaved by γ-secretase [77], and the resulting reduced cell surface level of BCMA and increased serum level of soluble BCMA could potentially limit the efficacy of BCMA-directed adoptive T-cell therapy by inhibiting CAR T-cell recognition of BCMA on myeloma cells [33,78,79]. Therefore, targeting other members in this ligand-receptor subgroup such as TACI, either alone or in combination with BCMA-targeting therapies, might achieve better clinical efficacy or improve the treatment outcome for MM patients.…”
Section: Targeting Taci In Immunotherapy Against MMmentioning
confidence: 99%